12. Bronchopulmonary dysplasia in extremely preterm infants: Prevalence and related factors - Van, Nguyen Thi; Linh, Tran Dieu; Trac, Le Minh (Tạp chí Nghiên cứu Y học, 2024)
Infants born extremely preterm are defined as a birth under 28 weeks gestational age. Bronchopulmonary dysplasia (BPD) is the most common lung complication in this population and manyfactors can contribute to the development of BPD. The objective of this study was to identify the prevalence of BPD and to analyse the related factors of BPD in extremely preterm infants. Seventy two infants who met the inclusion criteria were included in the study. BPD was diagnosed according to Jobe and Bancalari definition. The prevalence of BPD was 79.2%. There was an inverse relationship between the percentage of BPD, the severity of BPD and the gestational age and birth weight. Invasive ventilation requirement of more than 7 days was the independent factor of BPD. Conclusion: The prevalence of BPD was high. Prolonged invasive ventilation was an independent factor of BPD.